Variations in the Thickness of the Plantar Fascia After Training Based in Training Race. A Pilot Study - Alabau-Dasi, Raquel; Nieto-Gil, Pilar; Ortega-Ávila, Ana Belén; Gijón-Noguerón, Gabriel (Elsevier, 2020)
Plantar fascia (PF) is a connective tissue made up of mostly type 1 collagen that is subjected to constant loads. This study evaluated the effect of continuous running on tissue stress in the PF by measuring changes in the thickness of the PF using ultrasound scans. It was a cross-sectional study involving 24 runners from the University of Valen- cia, recruited as volunteers between December 2018 and February 2019. A variety of data was recorded: (age, body mass index, type of footwear, number of workouts per week, KM run per week, sports injuries in the last year, pre and postrace ultrasound PF measurements). There were significant differences in the 3 postrace meas- urements of the left foot (<0.001). PF thicknesses were measured before and after running, with a minimal average difference of 0.4 mm in the medial and central fascicles, and 0.3 mm in the lateral fascicle. We observed PF thick- nesses above 4mm in asymptomatic patients with no signs of vascularisation, proving that increased PF thickness is not the only criterion for diagnosis of plantar fasciitis.
Keywords: Pies - Lesiones y heridas; Plantar fascia; Runners; Tissue stress; Ultrasound measurement